Calidad microbiologica de un agua termal (2016)
Mineral waters of natural spas presents high diversity of microorganisms, which depends on its physicochemical properties such as temperature, pH, composition, among others. This article describes the results of the evaluation of the sanitary quality of hot springs pool "Estación Los Volcanes" and review of national and international quality standards for hot springs. The presence of heterotrophic bacteria, total coliforms, Escherichia coli and Pseudomonas aerugionosa in hot springs pool was evident, which indicates the advisability of implementing the health control measures in these types of establishments.